A Model of Multiple Equilibria in Geographic Labor Mobility - Ubeda, Luis (IMF Working Papers; Working Paper, 2002)
We develop a model of double matching in the labor market and the social environment in order to explain different migration patterns in response to local economic shocks. This approach explains the different behaviors of workers in different groups, regions, or countries in an endogenous way by showing the existence of multiple equilibria, rather than in an exogenous manner by introducing ex-ante regulations or unemployment benefits. This model can also explain why individuals from some communities form 'sister' communities in some cases and not in others.